Pengaruh Tekanan Waktu, Risiko Audit, dan Prosedur Review & Kontrol Kualitas Terhadap Penghentian Prematur Atas Prosedur Audit (Studi Empiris Pada KAP di Surakarta dan Yogyakarta) - Nurtiyani, Ani, Drs. Wahyono, MA, Ak (2015)
The research aimed to analyse the influence of time pressure, audit risk, review procedure and quality control to premature sign-off of audit procedure. This conduct will create a situation that usually called as reduced audit quality behaviors. The population of this research are all auditors working on the CPA's of the relic in Surakarta and Yogyakarta. While the sample of this research are some of the auditor's working relic in Surakarta and Yogyakarta. Determination of samples by using purposive sampling method. The data that used by this research is primary data, it was collected by questionnaires. The questionnaire was distributed to a number of 50-50 the questionnaire and everything can be processed. This research used multiple regression analysis. The results of this study indicate that the pressure of time, the risk of premature cessation of effect on audit upon audit procedures. Whereas the review procedure & quality control has no effect on the premture termination upon audit procedures. Keywords: premature sign-off audit procedures, time pressure, audit risk, review procedures and quality control.